Heterotopic ossification following hip arthroplasty: a comparative radiographic study about its development with the use of three different kinds of implants. Issue 1 (December 2015) - Biz, Carlo; Pavan, Davide; Frizziero, Antonio; Baban, Ala; Iacobellis, Claudio
Abstract Background Our purpose was to record the incidence of heterotopic ossification (HO) following hip replacement by different variables to identify patient groups that are likely to develop HO in the absence of a prophylactic protocol. Methods Radiographically, we studied 651 patients having undergone hip joint replacement, evaluating three kinds of implants:ceramic-ceramic-coupled total hip replacement (THR), TriboFit ® with polycarbonate urethane-ceramic coupling andendoprosthesis . Each patient was analysed for HO development by age, gender, diagnosis, presence of previous ossifications, surgical approach and kind of implant. Within the population that developed HO, data were assessed for correlation with severity of ossification graded according to Brooker classification. Results The overall incidence of HOs was 59.91 %. The factors increasing their incidence in the univariate analysis were as follows: lower age of the patients with HO (mean 77.6 years, p  = 0.0018) than those subjects who did not develop HO (mean 80.2 years); male gender (64.4 %, p  = 0.1011); diagnosis of coxarthrosis (72.7 %, p  = 0.0001) compared to femur neck fracture (55.9 %, p  = 0.0001); presence of previous HO (76.2 %, p  = 0.0260); lateral approach (65.5 %) as opposed to anterior-lateral approach (55.6 %, p  = 0.0163); and ceramic-ceramic THR (68.1 %) and TriboFit® (67.0 %) compared to endoprosthesis (51.3 %, p  = 0.0001). During multivariate analysis, the presence of HO after previous hip surgery (p  = 0.0324) and the kind of implant (p  = 0.0004) showed to be independent risk factors for the development of HO. Analysing the population that developed HO, we found that the severity of ossification by Brooker classification was influenced by gender (p  = 0.0478) and kind of implant (p  = 0.0093). Conclusions In agreement with the literature, our radiographic study confirms the following risk factors of HO development in absence of any prophylactic treatment: male gender, diagnosis of coxarthrosis compared to femur neck fracture, previous HO, surgical approach and kind of implant. In particular, Hardinge-Bauer and Watson-Jones surgical approaches, characterized by a wide exposure of the coxofemoral joint, and ceramic-ceramic THR and TriboFit® implants significantly increase the development of HO.